A hybrid method for the calculation of the inductances of coils with and without deformed turns. Issue 4 (4th July 2016) - Li, Hua; Rucker, Wolfgang
Abstract : Purpose: – The purpose of this paper is to present an accurate and efficient hybrid method for the calculation of the inductance of a coil and its inductance change due to deformed turns using numerical methods. Design/methodology/approach: – The paper opted for finite element method coupled with analytical method (FCA) to accurately calculate the inductance of a coil, which is used as reference value. An algorithm with a power function is presented to approximate the partial inductance matrix with the purpose of obtaining the percentage change of the inductance due to deformed turns by using the partial element equivalent circuit (PEEC) with an approximated model and an optimization process. The presented method is successfully validated by the numerical results. Findings: – The paper provides a systematic investigation of the inductance of an arbitrary shaped coil and shows how to accurately and efficiently evaluate the inductance change of a coil due to its deformed turns. It suggests that the inductance of a coil can be accurately calculated by using FCA and its percentage change due to deformed turns can be efficiently calculated by using the PEEC_Approximation. Research limitations/implications: – As this research is for the magnetostatics, the skin- and proximity-effects have not been taken into account. Practical implications: – The paper includes implication for the worst-case analysis of the coil's inductance due to mechanical damage or manufacturing tolerance. Originality/value: – This paper fulfills an identified need to study how the inductance change of a coil can be obtained accurately and efficiently.